2014
DOI: 10.1038/cddis.2014.278
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of apoptotic Bax translocation to the mitochondria is a central function of parkin

Abstract: Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder, affecting 1–3% of the population over 65. Mutations in the ubiquitin E3 ligase parkin are the most common cause of autosomal recessive PD. The parkin protein possesses potent cell-protective properties and has been mechanistically linked to both the regulation of apoptosis and the turnover of damaged mitochondria. Here, we explored these two functions of parkin and the relative scale of these processes in various cell types. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 63 publications
(109 reference statements)
5
50
1
Order By: Relevance
“…Our hypotheses are strengthened by recent reports showing that primary cultured neurons from Parkin knock-out mice accumulated greater levels of Bax at the mitochondria than wild type neurons after apoptotic stimulation [39]. The reduced Bax levels observed in human VSMC-overexpressing Parkin, seems not involved effects on transcription, but rather required Parkin-dependent ubiquitination of Bax and proteasomal degradation [30,40]. Therefore, we cannot exclude the coexistence and cooperation of both Parkin-dependent www.impactjournals.com/oncotarget regulations of mitochondrial clearance and apoptotic pathways within the same cells.…”
Section: Discussionsupporting
confidence: 65%
“…Our hypotheses are strengthened by recent reports showing that primary cultured neurons from Parkin knock-out mice accumulated greater levels of Bax at the mitochondria than wild type neurons after apoptotic stimulation [39]. The reduced Bax levels observed in human VSMC-overexpressing Parkin, seems not involved effects on transcription, but rather required Parkin-dependent ubiquitination of Bax and proteasomal degradation [30,40]. Therefore, we cannot exclude the coexistence and cooperation of both Parkin-dependent www.impactjournals.com/oncotarget regulations of mitochondrial clearance and apoptotic pathways within the same cells.…”
Section: Discussionsupporting
confidence: 65%
“…Some experiments showed that Bax is an important regulator of apoptotic neurodegeneration and that Bax plays a pivotal role in the destruction of dopamine-producing neurons in a mouse model of PD [39]. In MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-injected mice Bax expression levels were increased in regions specifically affected by the neurodegeneration processes [39,40]. So far, Naoi et al demonstrated the cell death caused by salsolinol in human dopaminergic neuroblastoma SH-SY5Y cells to be apoptotic [18].…”
Section: Discussionmentioning
confidence: 99%
“…Together, this highlights the likely possibility that PINK1 and Parkin have both dependent and independent functions and the possibility that some of these functions are distinct from mitochondrial autophagy. Additional examples of independent and distinct functions include Parkin regulation of mitochondrial cytochrome c release, BAX translocation to mitochondria, and apoptosis (Berger et al 2009; Johnson et al 2012a; Johnson et al 2012b; Charan et al 2014), and PINK1 regulation of neuronal dendritic morphology (Dagda et al 2014). …”
Section: Alternative Functions and Potential Pathogenic Mechanismsmentioning
confidence: 99%